SPECIES DIVERSITY AND DISTRIBUTION OF SPONGES IN THE COASTAL AREA OF KASIAK ISLAND PARIAMAN REGENCY SUMATERA BARAT PROVINCE - Ananda, Nahdya Nasri; Efriyeldi, Efriyeldi; Thamrin, Thamrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
Sponges are the most primitive multicellular animals that live in various types of waters from freshwater, brackish and sea. Sponges live in bottom waters that typically stick themselves on hard substrate such as rock or coral and compete with other tacks organism to obtain a food hall. The research was conducted in Kasiak Island Pariaman regency West Sumatera in February-March 2019, aims to find outthe type, density, frequency of occurrence, diversity index, dominance index, the distribution pattern of sponge, To support the research data is also observed the characteristics of the environment such as water quality. The method used is survey method, where sampling using belt transect method performed on three stations. The research found 14 genus / species of sponge consisting of 11 families in island waters Kasiak with sponge density values obtained in each research station ranges from 1458-4208 ind / ha. The highest frequency of occurrence of the type Jaspis sp. with the frequency of occurrence of 100%. Diversity index values ranged from 1.8921 to 1.9488, dominance index value obtained was from 0.3163 to 0.3396, and the value of the distribution pattern of the sponge ranges from 0.2941 to 0.3015.